Considering the Validity and Reliability Testing of a Digital Punch Measuring Tool in Young Combat Athletes - Budijono, Agung Prijo; Puspitaningayu, Pradini; Kurniawan, Wahyu Dwi; Firmansyah, Awang; Ayubi, Novadri; Arsapakdee, Kritchapol; Putro, Andika Bayu (Physical Education Theory and Methodology, 2024)
Objectives. The application of technology in sports, including combat sports, is increasing rapidly. This study aimed to determine the validity and reliability of digital punch-measuring tools in young combat athletes. Materials and methods. A total of 28 participants, consisting of 9 males (age 15.88 ± 1.6 years, height 162.56 ± 6.8 cm, weight 55.2 ± 10.2 kg, BMI 20.7 ± 2.5, PBF 14.57 ± 4.5 %) and 19 females (age 14.5 ± 1.5 years, height 154.3 ± 5.4 cm, weight 48.6 ± 8.5 kg, BMI 20.4 ± 3.2, PBF 27.4 ± 6.5 %) from the martial arts branch involved in the study and were included in data collection. The method used in this study was the Pearson Product-Moment Correlation Coefficient, analyzed using Minitab version 21. All research subjects engaged in a warm-up routine before performing three punches with both their right and left arms. Results. The findings of this study indicate positive validity (right 0.856, left 0.875) and reliability (right 0.8037, left 0.8209) in measuring both right and left punches. Conclusions. Thus, digital punch measuring tools can be used for training to improve punches and as an initial test tool for implementing effective training programs and monitoring the development of combat athletes.